2016
DOI: 10.3329/jsr.v8i2.26791
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polysilsesquioxanes with Double-Decker Silsesquioxane Repeating Units

Abstract: Polysilsesquioxanes were synthesized with end functional double-decker silsesquioxanes (DDSQ) and the polymers were characterized with 1 H NMR, 29 Si NMR and size exclusion chromatography (SEC). Polysilsesquioxane containing iso-butyl end capped DDSQ showed better solubility compared to that of methyl end capped DDSQ. Thermal properties investigated with TGA showed that the polymers exhibited exceptionally high stabilities in the range of 470-530°C even in both nitrogen and air atmosphere. The average residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Sodkhomkhum et al [66] reported the synthesis of poly(siloxane/B-POSS) via a polycondensation reaction between chlorides containing B-POSS and hexamethyltrisiloxane with high T g and transparency. Iso-butyl end-capped B-POSS reported by Groch et al [67] showed enhanced solubility compared with methyl end-capped B-POSS. Thermal properties investigated by thermogravimetric analysis (TGA) showed that the polymers had exceptionally high thermal degradation temperature (T d ) in the range of 470-530 • C whether in nitrogen or air atmosphere.…”
Section: Introductionmentioning
confidence: 95%
“…Sodkhomkhum et al [66] reported the synthesis of poly(siloxane/B-POSS) via a polycondensation reaction between chlorides containing B-POSS and hexamethyltrisiloxane with high T g and transparency. Iso-butyl end-capped B-POSS reported by Groch et al [67] showed enhanced solubility compared with methyl end-capped B-POSS. Thermal properties investigated by thermogravimetric analysis (TGA) showed that the polymers had exceptionally high thermal degradation temperature (T d ) in the range of 470-530 • C whether in nitrogen or air atmosphere.…”
Section: Introductionmentioning
confidence: 95%
“…Functionalized double-decker shaped silsesquioxane (DDSQ-2­(R 1 R 2 )) and corner capped cubic shaped silsesquioxanes (POSS-R 1 ) (Figure ) are cage-like silsesquioxanes with a dimensionally well-defined inorganic core, inert organic groups around the core which provides compatibility with the surround organic matter of interest, and exact specified reactive organic sites. , These structures have become model compounds to investigate effects of nanostructured inorganic additives on polymer properties. Applications of both DDSQ-2­(R 1 R 2 ) and POSS-R 1 nanostructures have been explored extensively. , , When used in organic polymers, the hybrid characteristics provide enhanced oxidation temperature, improved hydrophobicity, and low dielectric constant. ,,, Recent research extended the use of DDSQ-2­(R 1 R 2 ) and POSS-R 1 as supports to reduce the amount of packed bed required in heterogeneous catalysts. ,, Other applications for POSS-R 1 include improved ionic liquid performance and its thermal stability, , microstructure modifier to improve mechanical performance of metallic alloys, superhydrophobicity in coatings, , monomer for increased thermal and mechanical performance of thermosetting polymers, and use in pharmaceutical applications. , …”
Section: Introductionmentioning
confidence: 99%
“…Functionalized DDSQ structures can be obtained by reacting tetrasilanol octaphenyl double-decker shaped silsesquioxane (DDSQ-(Ph) 8 (OH) 4 ) 1 with functional chlorosilanes. When two equivalents of difunctional dichlorosilanes (R 1 R 2 SiCl 2 ) are used, generally a closed structure (DDSQ-2­(R 1 R 2 )) is obtained. ,, DDSQ-2­(R 1 R 2 ) has been explored for different applications such as amphiphilic molecules in Langmuir–Blodgett films, ionic liquids, or support for heterogeneous catalyst. , In addition, there are numerous studies using DDSQ-2­(R 1 R 2 ) in hybrid inorganic–organic polymers as the resultant hybrid polymers will contain the nanostructure as a part of the chain backbone. ,,,,− These hybrid polymers have shown enhanced hydrophobic properties, ,, low dielectric constants, ,, and improved thermo-oxidative stability without sacrifice of their mechanical performance. , …”
Section: Introductionmentioning
confidence: 99%